HARMONIC DISTORTION AS A REFERENCE FOR THE QUALITY OF THE ELECTRICAL DISTRIBUTION SYSTEM IN THE PT. GOJEK TOKOPEDIA LOGISTICS - Wiharja, Ujang; Slamet Purwo Santosa; Lukman Aditya (Universitas Lampung, 2025)
However, little research has been done on how harmonic distortion affects the electrical quality of buildings. This harmonic distortion is caused by nonlinear loads, which will mainly affect electronic equipment. At the building's main distribution panel point (MDP), To obtain information, total harmonic distortion in voltage (THD-v) and total harmonic distortion in current (THD-i) were measured directly. Regular Maintenance and checks will obtain data that can be evaluated so that the system is always reliable. In the case of the PT Gojek Tokopedia Indonesia building, the measurement results on 20-05-2023 showed that the number of THDi in phase R at MDP is 64.56%. According to the IEEE std 519-1992 standard, the permissible electric current is 15%, so in the solution with Harmonic Filter (H.F.), the change in electric current in phase R becomes 12.37%. Using a harmonic filter in the inductor (L) value of 0.28 mH and capacitor (C) value of 2 mF, The power factor increases to 0.99 from 0.85. Because of this, every building manager and Maintenance must pay regular attention to the THD value according to applicable standards.